2021
DOI: 10.1186/s12889-021-10341-7
|View full text |Cite
|
Sign up to set email alerts
|

Polytobacco product use among current cigarette smokers in Hong Kong, China: results from population surveys (2015–17)

Abstract: Background Polytobacco product use is increasingly popular, but little is known about the prevalence, trend, and factors of such use particularly in non-western countries. Method A representative sample of 1139 current cigarette smokers aged 15+ (84.1% male) were telephone interviewed in Tobacco Control Policy-related Surveys in 2015–2017. Information collected included poly-tobacco use (PTU), smoking and socio-demographic characteristics. Associat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 40 publications
1
3
0
Order By: Relevance
“…These results agree with the cigarette smoking rates among Chinese men reported in national surveys 1 , 3 . Furthermore, our findings support previous research, which has shown significant sex differences in regular cigarette use 3 , 15 , but we found a higher smoking rate among women than that reported in several previous studies 3 , 27 . These findings are worrying, considering the predicted number of deaths in China that will be caused by tobacco smoking in 2030 and 2050, if there is no decrease in this risky behavior 2 .…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…These results agree with the cigarette smoking rates among Chinese men reported in national surveys 1 , 3 . Furthermore, our findings support previous research, which has shown significant sex differences in regular cigarette use 3 , 15 , but we found a higher smoking rate among women than that reported in several previous studies 3 , 27 . These findings are worrying, considering the predicted number of deaths in China that will be caused by tobacco smoking in 2030 and 2050, if there is no decrease in this risky behavior 2 .…”
Section: Discussionsupporting
confidence: 92%
“…Polytobacco use can be defined as the concurrent use of regular cigarettes with other tobacco products, an emerging phenomenon among young adults in several regions of the world, including North America, Europe, and Asia 13 , 14 . In China, a study among smokers found that 15.9% were current poly users and of these 12.3% used one tobacco product in addition to regular cigarettes, and 2.5% used two tobacco products in addition to cigarettes 15 . Concerning health effects, polytobacco use has been shown to increase the risk of nicotine addiction and substance use disorders 16 .…”
Section: Introductionmentioning
confidence: 99%
“…However, newer forms of tobacco products like cigars, e-cigarettes, vaping pens and hukkah are on a rise [12,13], thus leading to poly-tobacco use. This has been defined as consumption of multiple tobacco or nicotine products [14,15] and is proving to be a serious threat to the public health [15,16]. A systematic review on nationally representative data from 48 countries on adult population has estimated that the poly-tobacco use is increasing in South-East Asia [17].…”
Section: Introductionmentioning
confidence: 99%
“…Despite that rates of cigarette smoking have been on the decline in recent decades in the U.S., the success of tobacco control efforts has been impeded by the diversification of tobacco products [3][4][5][6]. Recent research has demonstrated that the concurrent use of multiple types of non-cigarette tobacco products (i.e., cigars, smokeless tobacco, snuff, hookah, e-cigarettes, and pipes) is becoming increasingly common [7][8][9][10]. The increased variety of tobacco products in the commercial marketplace has been met with an alarming surge in demand that threatens decades of successful tobacco control efforts [4,5,[11][12][13].…”
Section: Introductionmentioning
confidence: 99%